The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3354/meps08769
|View full text |Cite
|
Sign up to set email alerts
|

Diet of juvenile southern elephant seals reappraised by stable isotopes in whiskers

Abstract: Declines in marine predator populations have been attributed to anthropogenic activity and environmental change. Southern elephant seals Mirounga leonina are major consumers of biomass in the eastern region of the Southern Ocean and have been declining in numbers since the 1960s. Previous studies have identified evidence for habitat and diet partitioning over a range of spatial and temporal scales between juveniles and adults in the Macquarie Island population. We first analysed the stable isotopes (SI) of 6 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 57 publications
(94 reference statements)
5
58
0
1
Order By: Relevance
“…Vibrissae are often subsampled into 2 mm segments for isotopic analyses (e.g., Newland et al 2011;Walters et al 2014), and we therefore reported the average number of days represented by a 2 mm vibrissal segment to emphasize the temporal resolution of the biogeochemistry data obtainable from sequentially sampled vibrissae.…”
Section: Growth Rate Of Re-sampled Vibrissaementioning
confidence: 99%
See 4 more Smart Citations
“…Vibrissae are often subsampled into 2 mm segments for isotopic analyses (e.g., Newland et al 2011;Walters et al 2014), and we therefore reported the average number of days represented by a 2 mm vibrissal segment to emphasize the temporal resolution of the biogeochemistry data obtainable from sequentially sampled vibrissae.…”
Section: Growth Rate Of Re-sampled Vibrissaementioning
confidence: 99%
“…To ensure that the SI signature is represented similarly across different vibrissae grown at the same time, we compared the SI profile of two vibrissae collected simultaneously from a third individual (hereafter, Seal 3, 0.8 yo) and eight vibrissae collected from a deceased adult female SES (hereafter, Seal 4) (see Lewis et al (2006) and Newland et al (2011)). We controlled for different vibrissa lengths and growth rates in Seal 4 (Greaves et al 2004;Beltran et al 2015) by applying the growth rate of adult M. angustirostris from Beltran et al (2015), using the maximum length of each of the sampled vibrissae as the asymptotic length in the equation.…”
Section: Testing Assumptions Regarding Vibrissal Growth Using Stable mentioning
confidence: 99%
See 3 more Smart Citations